Computer-supported collaborative learning best practices and principles for instructors - Orvis, Kara L.; Lassiter, Andrea L. R. (Gale virtual reference library, 2007)
Explores techniques that facilitate effective collaborative learning in virtual environments. Provides information on the role of the instructor in computer-supported collaborative learning, real-world perspectives on virtual learning group collaboration, and supporting learning group motivation.